The ketogenic diet in schizophrenia - Maciej Ćwiek; Anna Maria Bigdoń; Przemysław Gorczyca; Mateusz Góra; Adrian Krzysztof Hunek; Martyna Kozłowska; Rafał Kreft; Patryk Sydor; Marcel Wartacz; Aleksander Woźniak (Kazimierz Wielki University, 2023)
Schizophrenia is a mental illness that manifests itself in the second or third decade of life with no coherent aspect. The primary pharmacological therapy is antipsychotic medication, which mostly work by suppressing the activity of dopamine. Unluckily, many of schizophrenic patients experience hardship from severe positive or negative symptoms that can not be completely treated with available treatment. Last theory of schizophrenia mechanism contain systemic and central proinflammatory process, in brain glutamatergic neurotransmission and impaired systemic and cerebral energy metabolism. Ketogenic diet is firm controlled high-fat, low protein, low-carbohydrate diet, with lipid to non lipid ratio 4:1. Main mechanism is to cause ketosis. The situation in which ketones bodies are used as a substrate to generate energy in the organism. It could be that a ketogenic diet could help to compensate for the imbalance of GABA levels in schizophrenic brain. The ketogenic diet as an addition to drug treatment, hopefully may offer therapeutic opportunities to better result of the disease concerning symptomatology and preventing the gain of weight, due to some medication side effects or comorbidities.